On level sets of a pseudoharmonic function on a plane - Polulyakh, Ye.O. (Reports of the National Academy of Sciences of Ukraine, 2014)
Let T be a forest, which consists of a finite number of locally finite trees. Let V0 be the set of all vertices of T of degree 1. We propose a sufficient condition for the image of an embedding Ψ: T V0 → R2 to be a level set of a pseudoharmonic function.